(untitled) - Reiner, Miriam (New York, 1941)
This book started with a few directions for internes who were called upon to perform blood sugar, urea, carbon dioxide content as emergency procedures, usually in the middle of the night.
Keywords: Chẩn đoán, phòng thí nghiệm,Pharmaceutical chemistry,Diagnosis, Laboratory,Hóa dược; Laboratory manuals,Hướng dẫn thí nghiệm